AuriCheeks: Assistive Technology to Assist in Desktop Navigation - Neves Filho, Petrucio De Carvalho; Almeida Feitosa, Carlos Eduardo; Sousa Barreto, Juliana; Martins da Silva, Marcelo (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
With the increasing effectiveness of various technologies, several devices have been introduced to help people in their daily lives. In this study, we present AuriCheeks, it functions to aid tetraplegics or amputees in navigating on desktop computers, and it is a combination of an ear-worn equipment with the functions of a mouse. It has sensors that capture the movements of the user’s head and process this data in real time. We conducted a performance evaluation and observation. In our findings, we managed to reach a sensitivity rate of 80%, specificity of 76.66%, and a precision level of 77.41%.